ANALYSIS OF OPTIONAL QUALITY TERM (OQT): MOUNTAIN LABEL FROM PRODUCER’S PERSPECTIVE: STUDY OF MOUNTAINOUS COUNTIES SURROUNDING BRAȘOV, ROMANIA - Kiran MAINALI; Felix H. ARION; Cătălina ROGOZAN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Mountain products have been introduced in the EU supplemented with governing regulations to mainstream the products originating from mountain areas with adequate market facilities and use as a differentiating tool compared with conventional products. Since its formalisation and adoption of relevant laws in the national context in Romania, the adoption of the optional quality term Mountain Label among the producers has been astonishing. Considering the good market in Romania for quality and locally sourced products, mountain labels and their use among the producers were regarded as having a better impact on the economic and market status. The research intended to pursue an answer in the same direction to see if producers were able to fully exploit the EU optional quality term Mountain Label scheme at the national level in Romania or if there was dissatisfaction among the producers with the rules of utilizing the label. A general producer survey with questionnaires was planned, organized, and implemented on the three mountain massifs surrounding Brașov city to elicit the necessary findings. Due to continuous support from the relevant authorities in the registration of the label, the producers were interested in enlisting themselves in the quality scheme; however, poor marketing and promotional assistance were some of the problems identified as general problems that caused the producers to be disappointed in the labelling scheme. Although most of the producers had a good idea of the benefits associated with the label, only 50% of them were engaged in some way in highlighting the mountain label in their promotional activities. Different statistical tests like the U-test, correlation analysis, and chi-square tests were used in conjunction with the different findings visualisations to derive insightful findings. The findings of the research can be beneficial to comprehend existing scenarios of mountain labels and producers’ perceptions of mountain labels post-registration, propose different systematic reformations for better efficiency of operations of mountain labels, and realize its initial objectives.